Persepsi Terhadap Peranan Whitsleblowing dalam Meningkatkan Integriti Anggota Polis Diraja Malaysia: Satu Kajian ke atas Kontinjen Perak - Megat Ayop, Megat Arifin (2010)
The study aims to survey the perceptions of Royal Malaysian Police (RMP) on whistleblowing in enhancing integrity among the members of Perak contingent. The sampling technique used is simple random sampling. The instrument is questionnaire. The data was analyzed using Statistical Package for Social Science (SPSS) Version 17.0. The research findings revealed that there is a significant difference on perceptions on integrity on demography aspects such as gender, level of education, rank, location and years of services. The correlation test to measure the relationship between perception on whistleblowing and integrity shows a significant value thus lead to a conclusion that there is a significant relationship between perception on whistleblowing and perception on integrity. However there is no significant different between perceptions on whistleblowing and the impact of reporting. It can be concluded that RMP members have a positive perceptions on whistleblowing thus a positive measures must be considered by the government to implement whistleblowing in RMP services.